Taxing wages 2013 (Paris, 2013)
"Taxing Wages provides unique information on the taxes paid on wages in OECD countries. It covers personal income taxes and social security contributions paid by employees; social security contributions and payroll taxes paid by employers and cash benefits paid by in-work families. The purpose is to illustrate how these taxes and benefits are calculated in each member country and to examine how they impact on household incomes. The results also enable quantitative cross-country comparisons of labour cost levels and the overall tax and benefit position of single persons and families on different levels of earnings.